Fluorescence quenching-based immunological probe for ticagrelor monitoring - Zhang, Shengshuo; Cheng, Yueqing; Gao, Yujie; Zou, Yujie; Xiao, Weiling; Li, Tianyi; Li, Mei; Yu, Bowen; Dong, Jinhua (Frontiers in Bioengineering and Biotechnology, 2023)
Ticagrelor is extensively utilized for the treatment of acute coronary syndromes (ACS), but its platelet aggregation inhibitory effects can potentially result in tissue bleeding, posing a serious risk to patients' lives. In this study, we developed highly sensitive full length anti-ticagrelor Quenchbodies (Q-bodies) for fast monitoring of ticagrelor both in solution and serum for the first time. Ticagrelor coupled with Nhydroxysuccinimide (Ticagrelor-NHS) ester was also designed and synthesized for interaction and biological activity detection. Both ATTO-labeled MEDI2452 (2452A) Q-body and TAMRA-labeled IgG 152 (152T) Q-body demonstrated efficient detection of ticagrelor and its active metabolite (TAM). The 2452A Q-body exhibited a broader detection range, while the 152T Q-body displayed a lower limit of detection (LOD).Under physiological conditions (Ticagrelor:TAM, 3:1), the concentration of ticagrelor was further measured, yielding LOD values of 4.65 pg/mL and 2.75 pg/mL for the two Q-bodies, with half-maximal effect concentrations of 8.15 ng/mL and 3.0 ng/mL, respectively. Compared with traditional liquid chromatography-mass spectrometry (LC-MS) methods, anti-ticagrelor Q-bodies have higher sensitivity and detection speed.It enabled the completion of analysis within 3 min, facilitating rapid preoperative detection of blood drug concentration in ACS to determine the feasibility of surgery and mitigate the risk of intraoperative and postoperative hemorrhage. The swift detection of ticagrelor holds promise for enhancing individualized drug administration, preventing adverse reactions, and providing preoperative guidance.